2019
DOI: 10.1215/21562261-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Gushel–Mukai varieties: Linear spaces and periods

Abstract: Beauville and Donagi proved in 1985 that the primitive middle cohomology of a smooth complex cubic fourfold and the primitive second cohomology of its variety of lines, a smooth hyperkähler fourfold, are isomorphic as polarized integral Hodge structures. We prove analogous statements for smooth complex Gushel-Mukai varieties of dimension 4 (resp. 6), i.e., smooth dimensionally transverse intersections of the cone over the Grassmannian Gr(2, 5), a quadric, and two hyperplanes (resp. of the cone over Gr(2, 5) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(117 citation statements)
references
References 24 publications
2
115
0
Order By: Relevance
“…In [DIM15] (see also [DK18a,DK16,DK18b]), similarly to Hassett's analysis of cubic fourfolds (see [Has99,Has00]), the authors studied Gushel-Mukai fourfolds via Hodge theory and via the period map. In particular, they showed that inside X 10 there is a countable union d GM d of (not necessarily irreducible) hypersurfaces parametrizing special Gushel-Mukai fourfolds, that is fourfolds [X] ∈ X 10 that contain a surface S whose cohomology class does not come from the Grassmannian G(1, 4).…”
Section: Introductionmentioning
confidence: 99%
“…In [DIM15] (see also [DK18a,DK16,DK18b]), similarly to Hassett's analysis of cubic fourfolds (see [Has99,Has00]), the authors studied Gushel-Mukai fourfolds via Hodge theory and via the period map. In particular, they showed that inside X 10 there is a countable union d GM d of (not necessarily irreducible) hypersurfaces parametrizing special Gushel-Mukai fourfolds, that is fourfolds [X] ∈ X 10 that contain a surface S whose cohomology class does not come from the Grassmannian G(1, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 4.5 ( [DK2,DK5]). Let X be a smooth GM variety of dimension n ∈ {3, 4, 5, 6}, with associated Lagrangian A.…”
Section: 3mentioning
confidence: 99%
“…The Hilbert schemes F d−1 (Q 1 (X)/P(V 5 )) were identified in [DK2,Proposition 4.1] with some irreducible components of the Hilbert schemes F d−1 (X) of (d − 1)-dimensional linear spaces on X. The connected fibers of its Stein factorization over P(V 5 ) were described in [DK2,Theorems 4.2,4.3,and 4.7].…”
Section: The Intersection Loci For the Lagrangian Subbundles Ofmentioning
confidence: 99%
“…give double EPW sextics and EPW cubes as special cases. These double covers also appear in the theory of Gushel-Mukai varieties ( [DK1,DK2]) and this was the original motivation for this work. In the relative situation (for the universal family of EPW varieties), a similar double cover is the base for a generalized root stack construction in terms of which the moduli stack of Gushel-Mukai varieties is described in [DK3].…”
Section: Introductionmentioning
confidence: 99%